Methodology of the Treatment of Pulmonary Tuberculosis - Frayt V.; Fedoriv Ya.-R. (Львівський клінічний вісник)
Introduction. Despite the significant successes of tuberculosis treatment, the epidemiological situation, which practically does not show a probable improvement ща the main epidemiological parameters, remains anxious. Aim. To increase the efficiency of treatment of patients with primary and recurrent pulmonary tuberculosis, as well as to prevent simultaneously the onset and progressing of chronic pulmonary heart (PH) on the basis of the complex of peculiarities of their pathogenic mechanisms, ascertained by us. Materials and methods. The relationships between tuberculosis and the average temperature in January, July, and during the whole year, respectively in 69 countries of the world, as well as the dependence of the morbidity on the average temperature in 23 countries in America, Africa and Europe were studied. The coefficient of correlation r between the incidence of tuberculosis and the average temperature of the enviroment and the degree of its probability p is calculated. The study of the course and manifestations of the disease with the simultaneous analysis of the important functional indicators in the process of antibiotic treatment of 717 patients aged from 15 to 78 years (average age 35.8 years), of which 452 men (63.0%) and 265 women (37.0%). Results. Hypotonia and hypovolemia are the main factors that not only lead to the onset of pulmonary tuberculosis and the formation of PH, but also lead to poor treatment efficiency. PH is formed, mainly due to hypotension and hypovolaemia, which are additionally induced by the reduced vascular tone and increased fluid loss. Correlation of the regional disorders of the main functions of the cardiopulmonary system, especially in conditions of increased blood supply, which was provided by the appointment of a gentle bed regimen in an anti-rheostatic position during the first 1.5-2.0 months of stay in the hospital, and an additional (up to 1.5-2.0 l per day), in combination with modern antibacterial drugs, not only prevents the formation of PH, but also significantly increases the effectiveness of treatment of the patients with primary and recurrent pulmonary tuberculosis. Conclusions. Chemotherapy in the patients with primary or recurrent pulmonary tuberculosis on the background of the advancing correction of the disorders of the main regional functions of the lungs (ventilation and perfusion) not only increases the efficacy of treatment but also prevents the recurrences of the disease and formation of chronic PH.